Better Photosynthesis in Rice (Oryza sativa L.) by Introduction of the C4 Pathway: an Evolutionary Approach Towards a Sustainable System - Sarkar, Sukamal; Sengupta, Kajal; Karim, Mir Jishan (International Journal of Bio-resource and Stress Management, 2016)
The 1st green revolution in the 1960s brought a rapid increase in the yield potential of rice up to more than 10 times that was sufficient to meet the then global food demand. In last four decades the yield of rice has not increased significantly, although the global population is growing rapidly. To meet food demand of this increasing global population, the production of rice must be increased by at least 50% within the next four decades compared to the present day’s cultivars. It can be made possible, only if we designed the rice photosynthesis as C4 type with the help of genetic engineering. It is proved that a C4 type of photosynthesis mechanism is more efficient than a C3 type found in all the present day’s cultivars of rice and it might help in increasing the yield potential by alteration of the photosynthetic behaviour of the crops like sorghum and maize. This novel process will help us in producing more grain yield as well as higher water and nitrogen use efficiency particularly in the hot and dry environments. This review paper provides all the recent development of the factors that need to be altered in rice, so that the C4 photosynthetic mechanism can be introduced successfully. Further the differences between the C3 and C4 type photosynthetic pathways in respect of anatomy, biochemistry and genetics are briefly discussed.